Potensi Abu Sekam Padi untuk Meningkatkan Ketahanan Oksidatif Non-enzimatik dan Produksi Padi Merah pada Cekaman Kekeringan - Rachmawati, Diah; Mona Monika, Ni Luh Gde; Masruroh, dan Ulfatul (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Drought inhibits several physiological process and induces oxidative stress due to the enhanced production of reactive oxygen species (ROS) mainly in photosynthetic apparatus. Silicon (Si) is known to increase tolerance of rice against drought stress. However, long period of intensive crop cultivation depleted the available soil Si by approximately 11-20%. Rice husk ash (RHA) is potential Si source. The objective of this research was to analyze the potency of RHA through pot experiment to observe: 1) internal water balanced; 2) integrity of cell membrane and antioxidant content; and 3) production of tolerant cultivar ‘Segreng’ and sensitive one ‘Cempo merah’. Application of RHA was at level of 0, 4, and 8 tons ha-1. Drought stress was imposed by with holding water until soil water content reached 50% of field capacity (moderate stress) and 25% of field capacity (severe stress). Application of RHA significantly increased leaf relative water content and membrane stability index of rice ‘Segreng’ and ‘Cempo merah’. Tolerant cultivar ‘Segreng’ had better response than ‘Cempo merah’ as shown by greater leaf relative water content under moderate and severe stress. RHA application at level of 8 tons ha-1 increased index of membrane stability and level of antioxidant (AAred and α-tocopherol) which determine production of both rice ‘Segreng’ and ‘Cempo merah’ during drought.Keywords: antioxidant, field capacity, membrane stability, segreng cultivar, α-tocopherol